1992
DOI: 10.1080/02772249209357797
|View full text |Cite
|
Sign up to set email alerts
|

Levels of polychlorinated biphenyls and polychlorinated dibenzofurans in the blood, subcutaneous adipose tissue and stool of Yusho patients and normal subjects

Abstract: An effective therapy which assists the elimination of the residual chlorinated compounds in Yusho patients has still not been established. To determine the behavior of polychlorinated biphenyls (PCBs) and polychlorinated dibenzofurans (PCDFs) in patients 20 years since the occurrence of Yusho disease, the concentrations of PCBs and PCDFs in the blood, subcutaneous adipose tissue and stools were investigated in six patients with typical symptoms of Yusho disease. The daily excretion levels of 2,3,4,7,8-pentachl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Surprisingly few studies have explored feces as a noninvasive matrix for biomonitoring. Several studies in adults of dietary absorption, body concentrations, and fecal elimination of polychlorinated dibenzo- p -dioxins and furans (PCDD/Fs), polychlorinated biphenyls (PCBs), and hexachlorobenzene (HCB) have shown that digestive absorption of hydrophobic organic chemicals (HOCs) is dependent on dietary intake, whereas fecal excretion is independent of dietary intake but dependent on body burden. This was postulated to be due to a two-stage process, called the “fat-flush” theory, whereby dietary lipids are first absorbed from the small intestine lumen into gut tissue, leading to subsequent reduction in gut tissue HOC concentrations. This change in chemical gradient then facilitates diffusion of HOCs from the small intestine lumen into the tissue and further distribution to the body’s fat reservoirs. When the lumen contents later reach the large intestine, the process is reversed and excretion of lipids from the body into the feces leads to a concentration gradient favoring diffusion of HOCs from the tissues into the feces.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly few studies have explored feces as a noninvasive matrix for biomonitoring. Several studies in adults of dietary absorption, body concentrations, and fecal elimination of polychlorinated dibenzo- p -dioxins and furans (PCDD/Fs), polychlorinated biphenyls (PCBs), and hexachlorobenzene (HCB) have shown that digestive absorption of hydrophobic organic chemicals (HOCs) is dependent on dietary intake, whereas fecal excretion is independent of dietary intake but dependent on body burden. This was postulated to be due to a two-stage process, called the “fat-flush” theory, whereby dietary lipids are first absorbed from the small intestine lumen into gut tissue, leading to subsequent reduction in gut tissue HOC concentrations. This change in chemical gradient then facilitates diffusion of HOCs from the small intestine lumen into the tissue and further distribution to the body’s fat reservoirs. When the lumen contents later reach the large intestine, the process is reversed and excretion of lipids from the body into the feces leads to a concentration gradient favoring diffusion of HOCs from the tissues into the feces.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the chl-chitosan was able to reduce the amount of dioxins stored in the body. Such a reduction is usually seen only when the intake is relatively small (60,(67)(68)(69)(70)(71).…”
Section: Effects Of Chitosan and Chl-chitosan On Dioxin Excretionmentioning
confidence: 99%
“…A range of POPs has been found in faeces in previous studies dating back to the 1990s from Yusho patients (Iida et al, 1992). Following that, faecal POPs have been mainly measured in breast-fed infants where selected POPs were analysed in their faeces for calculating chemical absorption percentages against the ingested amount of POPs via breast milk (Jödicke et al, 1992;Korner et al, 1993;McLachlan, 1993;Abraham et al, 1996b).…”
Section: Potential Biomarker For Concentrations Of Pops In Blood (Cb)mentioning
confidence: 99%
“…Cb, itself, also serve as an important indicator of human body burden of POPs (Price et al, 1972;Iida et al, 1992;Rohde et al, 1999;Wolff and Anderson, 1999;Park et al, 2007;Stapleton et al, 2009). As outlined above, it is typically assumed that POPs are in passive pharmacokinetics equilibrium between different lipid compartments such as those of blood and adipose reservoir of the individuals.…”
Section: Assessing Concentrations Of Pops In the Blood (Cb) Of Infantmentioning
confidence: 99%
See 1 more Smart Citation